Toxic effects of Canavalia ensiformis L. (Leguminosae) on laboratory colonies of Atta sexdens L. (Hym., Formicidae) - Hebling, M. J. A. [UNESP]; Bueno, O. C. [UNESP]; Pagnocca, F. C. [UNESP]; Silva, O. A. da [UNESP]; Maroti, P. S. [UNESP] (Blackwell Wissenschafts Verlag Gmbh, 2000)
Laboratory colonies of the leaf-cutting ants Atta sexdens that were fed daily with leaves of Canavalia ensiformis showed a high ant mortality, and a significant decrease in fungal garden volume, with complete depletion of nests after 11 weeks of treatment.
Keywords: Ant; Mortality; Toxicity; Formicidae; Hymenoptera